Patriarchal Dominance as a Contributor to Domestic Violence - Rismayadi, Dedi; Alimuddin, Alimuddin; Mustaqim, Riza Afrian (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
In a society still dominated by patriarchal views, women often face injustice and domestic violence, which hinders gender equality and leads to poverty. This phenomenon, which is often considered a private matter, is further exacerbated by a lack of legal understanding and suboptimal community responses. This study aims to explore in depth the dynamics of patriarchal domination and its impact on domestic violence at the micro level. Using a qualitative case study design in Gampong Cot Matahe, data was collected through in-depth interviews, observations, and documentation studies. The results showed that patriarchal structures are deeply rooted, leading to power imbalances and the normalization of domestic violence, with victims facing stigma and dependency. Although regulations exist, their implementation in the field is still weak due to a lack of legal awareness and the suboptimal role of community leaders in prevention and handling. This study contributes to an enriched understanding of the manifestations of patriarchy and domestic violence at the local community level, and suggests a comprehensive approach for more effective interventions.